The Effect of Touch and Sound Therapy to The Level of Pain and Physiological Parameters in Infants - Rafika Dora Wijaya; Tita Husnitawati Madjid; Enny Harliany Alwi (Universitas Muhammadiyah Yogyakarta, 2020)
Background: During hospitalization, infants are exposed to unpleasant stimuli such as stress, pain, noise, and invasive procedures. These stimuli produce significant changes in vital signs. Touch and sound therapies are a therapy given to the infants in the form of a mother's touch and a light pat on the baby's hands, feet, body, and head. This procedure is accompanied by rhythmic sounds that have been made in the form of audio files. Objective: This study aimed to determine whether touch and sound therapy can affect the level of pain and physiological parameter (heart rate, respiratory rate, and oxygen saturation) in infants by venous blood sampling.Method: This research is an experimental study with a control time-series design, which was conducted from July to October 2013. The research subjects are 30 infants aged 1-12 months who took venous blood samples. Research data were analyzed statistically by the t-test.Result: The results showed that the NIPS scores differed significantly between the intervention and control groups p = 0.000 (p 0.05). Heart rate has a significant effect between the intervention and control groups p = 0.011 (p 0.05). The respiratory rate in the intervention group was lower compared to the control group p = 0.033 (p 0.05). There was no significant difference in oxygen saturation between the intervention and control groups p = 0.232 (p0.05).Conclusion: Touch and Sound therapy decrease levels of pain, heart rate, and respiratory rate, but does not affect oxygen saturation.